The role of International Organization of the Francophonie in implementing the principle of the responsibility to protect - Benouna, Redha; Boulemkahel, Ahmed (Journal of Human Sciences, 2021)
This article discusses the role of regional international organizations in the implementation of the principle of the responsibility to protect adopted by the United Nations at the 2005 World Summit, as an example of a case study of the International Organization of the United Nations. Francophonie as one of the pioneering organizations that adopted this concept by highlighting the institutional development in the objectives of the organization of the cultural and linguistic function to the political position. It allowed the organization to adopt the principle of the responsibility to protect and contribute to the settlement of international disputes in accordance with the principle of prevention.